Artificial clicks (Porpoise ALert) affect acoustic monitoring of harbour porpoises and their echolocation behaviour - Schnitzler, Joseph G.; Moysan, Louise; Escobar-Calderon, Juan Felipe; Baltzer, Johannes; Schaffeld, Tobias; Kindt-Larsen, Lotte; Siebert, Ursula (Frontiers in Marine Science, 2025)
IntroductionIn 2021, a continuous acoustic monitoring programme was initiated in the Baltic Sea of Schleswig-Holstein to determine the occurrence and seasonal distribution of harbour porpoises. At the same time, fishers in this area applied acoustic devices (Porpoise ALert, PAL) generating artificial porpoise clicks to reduce bycatches in set-net fisheries. The underlying hypothesis was that signals from porpoise acoustic warning devices (PALs) might be misinterpreted by the click loggers (C-POD) as genuine porpoise clicks, potentially leading to an increase in detections. The study aimed to determine whether PALs were being recorded at the monitoring stations, and to identify effective methods for filtering out artificial signals.MethodsTherefore, we deployed an array of 11 C-PODs at distances between 50 and 350 m to a duty-cycled PAL in the middle over a period of 3 months. A sophisticated machine learning approach was employed that was able to discriminate natural porpoise signals from artificial PAL signals using the full click sequence parameters.ResultsThe trained algorithm showed remarkable efficiency in discriminating between artificial PAL signals and natural harbour porpoise clicks, demonstrating good sensitivity (99.74%) and accuracy (97.12%) in the test dataset.DiscussionThe consequences for compromised monitoring are significant, particularly in regions with low harbour porpoise densities, where artificial signals may influence the interpretation of diurnal and seasonal aspects of natural harbour porpoise behaviour, leading to misinterpretations. The effectiveness of management measures depends on the availability of reliable monitoring data, which is essential given the urgent need to improve the conservation of harbour porpoises, which are declining in the western Baltic Sea within the waters of Schleswig-Holstein. Finally, the study design was maximised to provide further information on PAL functionality and effectiveness as warning devices. The results revealed a reduction in the number of porpoise clicks during PAL operation, and changes in echolocation patterns characterised by increased minimum Inter-click-intervals (ICI), suggesting a shift from foraging or communication to orientation activity, and decreased maximum ICI, indicating enhanced long-range orientation. The function of these devices on echolocation behaviour remains therefore unclear, as it is not known whether they act solely as an alarm or rather as a deterrent.